The Effect of Financial Literacy and Payment Gateway on Financial Performance in MSMEs in Palembang City - Dwiana, Handina; Gunarto, Muji (International Journal of Finance Research, 2024)
This research, aimed at testing the influence of financial literacy and payment gateways on the financial performance of MSMEs in Palembang, yields significant findings. The sampling technique, non-probability with purposive sampling, was employed to gather data from 100 respondents in the culinary subsector MSMEs in Palembang. The research method, a quantitative approach involving the distribution of questionnaires, was used. The data analysis, facilitated by SmartPLS 3 software, included the evaluation of measurement models, structural models (inner models), and hypothesis testing. The research results, which are of paramount importance, reveal that financial literacy has a positive and significant effect on financial performance, payment gateway has a negative and insignificant effect on financial performance, financial literacy has a positive and significant effect on payment gateways, and payment gateways are unable to mediate and have a negative impact between financial literacy and financial performance